Scenarios : Aguirre, the wrath of god ; Every man for himself and god against all ; Land of silence and darkness ; Fitzcarraldo - Herzog, Werner, 1942- (University of Minnesota Press, 2017)
Werner Herzog doesn't write traditional screenplays. He writes fever dreams brimming with madness, greed, humor, and dark isolation that can shift dramatically during production--and have materialized into extraordinary masterpieces unlike anything in film today. Harnessing his vision and transcendent reality, these four pieces of long-form prose earmark a renowned filmmaker at the dawn of his career.